Seed maturation indices for better regeneration and multiplication of haldu (Adina cordifolia) - JEENA, L S; KAUSHAL, R; DHAKATE, PARAG M; TEWARI, SALIL K (The Indian Journal of Agricultural Sciences, 2012)
Haldu (Adina cordifolia Roxb.) is one of the common associate species in moist mixed deciduous forests. In Western Himalayas, it is confined to outer slope up to 1000m. The wood of the species is used for making doors and window frames, plywood. The species is also heavily exploited for fuel wood and fodder. Fruits of Adina cordifolia were collected from four collection sites, (viz Tanda range, Bhakara range, Barheni range and Lalkuan range at five different collection dates, viz 1st week of April, 2nd week of April, 3rd week of April, 4th week of April and 1st week of May) for assessing seed maturation indicators. The results revealed significant variation in collection date and collection site for germination parameters. The change in fruit colour of A. cordifolia from light green to light brown and moisture content of fruit between 38 to 46% was adjudged useful indicator of seed maturation. Germination was maximum in seeds collected during first week of May at all the sites.